Risk-Neutral Skewness, Informed Trading, and the Cross Section of Stock Returns - Chordia, Tarun; Lin, Tse-Chun; Xiang, Vincent (Journal of Financial and Quantitative Analysis, 2021)
Abstract In this article, we use volatility surface data from options contracts to document a strong, robust, and positive cross-sectional relation between risk-neutral skewness (RNS) and subsequent stock returns. The differential return between high- and low-RNS stocks amounts to 0.17% per week. Preannouncement RNS is positively related to earnings announcement returns, and the positive RNS–return relation is more pronounced for other nonscheduled news releases. This suggests that it is informed trading that drives the positive relation between RNS and subsequent stock returns. We also find that RNS contains incremental information beyond trading signals captured by option-implied volatility and volume.